Analisis Pengaruh Faktor Keuangan Dan NonKeuangan Terhadap Peringkat Obligasi(Studi Empiris Pada Perusahaan Non KeuanganYang Terdaftar Di Bursa Efek Indonesia periode 2012 - 2014 - Rif'anzaki, Muhammad; , Fauzan S.E., M.Si., Ak (2016)
Bond rating useful for investors and issuers, which provide information about the company's ability to pay the bond issued. This research aimed to explain finacial and non financial factors that affect bond rating. Independent variables were examined are: (1)profitability, (2) liquidity, (3) Solvability, (4) leverage, (5) maturity, and (6) secure (bond give or not). The sample of this research is bonds of the non finance companies listed in Indonesia Stock Exchange and rated by rating agency PT PEFINDO period 2012 - 2014. Criteria of selected samples using purposive sampling method. Total sample were collected 37 bonds from 19 non finance companies during the year 2012 - 2014. Testing the hypothesis using an ordinal logistic regression analysis (PLUM) because the dependent variable is ordinal scale (rating). The result of this research indicate that independent variable Solvability, leverage, Maturity, and secure affect bond rating on 0,05 level significant. But independent variable Profitability and liquidity has no affect on bond rating. Keyword: Bond Ratings, Profitability, Liquidity, Solvability, Leverage, Maturity, Secure, Ordinal Logistic Regression.